Modeling carbon budgets in conventional and diverse crop rotations with cover crops using eddy covariance data - Agustin J. Olivo; Brian B. Grant; Patrick K. C. Pow; Ward N. Smith; Claudia Wagner-Riddle (Agricultural and Forest Meteorology, 2026)

Heat waves associated with higher methane emissions from dairy manure: A 6-year study - Andrew VanderZaag; Hambaliou Baldé; Thomas K. Flesch; Chih-Yu Hung; Claudia Wagner-Riddle (Agricultural and Forest Meteorology, 2026)

Inclusion of the social costs of N2O emissions increases the financial benefits from N inhibitor use on corn production in Ontario, Canada - Obed Teye Sappor; Aaron De Laporte; Azeem Tariq; Alfons Weersink; Brian Grant; Ward Smith; Claudia Wagner-Riddle (Field Crops Research, 2025)

Net ecosystem carbon budget and net greenhouse gas emissions under diverse crop rotation using cover crops compared to a conventional crop rotation - Keerthika N. Ranathunga; Jacob Evans; Nikolett Toth; Shannon Brown; Laura L. Van Eerd; Claudia Wagner-Riddle (Agriculture, Ecosystems & Environment, 2025)

Combining measurements and modelling to reveal long-term effects of nitrogen fertilizer application timing on N2O emissions in corn - Jongwon Kang; Pedro Vitor Ferrari Machado; David Hooker; Brian Grant; Ward Smith; Claudia Wagner-Riddle; Joshua Nasielski (Field Crops Research, 2025)

Cover crops increase belowground N retention substantially in corn cropping systems: Results from a 15N residue swapping experiment - Spencer M. Heuchan; Claudia Wagner-Riddle; Khagendra R. Baral; Katelyn A. Congreves; Richard E. Farrell; Sean Jordan; Hugh A. L. Henry (Plant and Soil, 2025)

Adaptive multi-paddock grazing increases soil carbon stocks and decreases the carbon footprint of beef production in Ontario, Canada - Jessica Mehre; Kimberley Schneider; Susantha Jayasundara; Adam Gillespie; Claudia Wagner-Riddle (Journal of Environmental Management, 2024)

Increased N2O emissions by cover crops in a diverse crop rotation can be mediated with dual nitrification and urease inhibitors - Azeem Tariq; Nicole Menheere; Yuanpei Gao; Shannon Brown; Laura L. Van Eerd; John D. Lauzon; Sander Bruun; Claudia Wagner-Riddle (Agriculture, Ecosystems & Environment, 2024)

Low-power flux gradient measurements for quantifying the impact of agricultural management on nitrous oxide emissions - Shannon E. Brown; Claudia Wagner-Riddle; Ben Conrad (Agricultural and Forest Meteorology, 2024)

Snow removal and cover crops influence soil nitrogen transfer to the subsequent corn crop - Spencer M. Heuchan; Claudia Wagner-Riddle; Hugh A. L. Henry (Plant and Soil, 2024)

Impacts of land use conversions on soil organic carbon in a warming-induced agricultural frontier in Northern Ontario, Canada under historical and future climate - Rong Jiang; Susantha Jayasundara; Brian B. Grant; Ward N. Smith; Budong Qian; Adam Gillespie; Claudia Wagner-Riddle (Journal of Cleaner Production, 2023)

Crop rotations differ in soil carbon stabilization efficiency, but the response to quality of structural plant inputs is ambiguous - Alison E. King; Katelyn A. Congreves; Bill Deen; Kari E. Dunfield; Myrna J. Simpson; R. Paul Voroney; Claudia Wagner-Riddle (Plant and Soil, 2020)

A 1-year greenhouse gas budget of a peatland exposed to long-term nutrient infiltration and altered hydrology: high carbon uptake and methane emission - Sina Berger; Elisa Braeckevelt; Christian Blodau; Magdalena Burger; Marie Goebel; Otto Klemm; Klaus-Holger Knorr; Claudia Wagner-Riddle (Environmental Monitoring and Assessment, 2019)

Surface and subsurface N2O losses from dairy cropping systems - Jessica Quesnel; Andrew C. VanderZaag; Anna Crolla; Christopher Kinsley; Edward G. Gregorich; Claudia Wagner-Riddle (Nutrient Cycling in Agroecosystems, 2019)

Micrometeorological measurements over 3 years reveal differences in N 2 O emissions between annual and perennial crops - Diego Abalos; Shannon E. Brown; Andrew C. Vanderzaag; Robert J. Gordon; Kari E. Dunfield; Claudia Wagner‐Riddle (Global Change Biology, 2016)
Perennial crops can deliver a wide range of ecosystem services compared to annual crops. Some of these benefits are achieved by lengthening the growing season, which increases the period of crop water and nutrient uptake, pointing to a potential role for perennial systems to mitigate soil nitrous oxide (N 2 O) emissions. Employing a micrometeorological method, we tested this hypothesis in a 3‐year field experiment with a perennial grass‐legume mixture and an annual corn monoculture. Given that N 2 O emissions are strongly dependent on the method of fertilizer application, two manure application options commonly used by farmers for each crop were studied: injection vs. broadcast application for the perennial; fall vs. spring application for the annual. Across the 3 years, lower N 2 O emissions ( P 0.001) were measured for the perennial compared to the annual crop, even though annual N 2 O emissions increased tenfold for the perennial after ploughing. The percentage of N 2 O lost per unit of fertilizer applied was 3.7, 3.1 and 1.3 times higher for the annual for each consecutive year. Differences in soil organic matter due to the contrasting root systems of these crops are probably a major factor behind the N 2 O reduction. We found that a specific manure management practice can lead to increases or reductions in annual N 2 O emissions depending on environmental variables. The number of freeze‐thaw cycles during winter and the amount of rainfall after fertilization in spring were key factors. Therefore, general manure management recommendations should be avoided because interannual weather variability has the potential to determine if a specific practice is beneficial or detrimental. The lower N 2 O emissions of perennial crops deserve further research attention and must be considered in future land‐use decisions. Increasing the proportion of perennial crops in agricultural landscapes may provide an overlooked opportunity to regulate N 2 O emissions.

Estimating a Lagrangian Length Scale Using Measurements of CO2 in a Plant Canopy - Shannon E. Brown; Jon S. Warland; Eduardo A. Santos; Claudia Wagner-Riddle; Ralf Staebler; Meaghan Wilton (Boundary-Layer Meteorology, 2013)

Minimizing nitrogen losses from a corn–soybean–winter wheat rotation with best management practices - Susantha Jayasundara; Claudia Wagner-Riddle; Gary Parkin; Peter von Bertoldi; Jon Warland; Bev Kay; Paul Voroney (Nutrient Cycling in Agroecosystems, 2007)

Intensive measurement of nitrous oxide emissions from a corn–soybean–wheat rotation under two contrasting management systems over 5 years - CLAUDIA WAGNER‐RIDDLE; ADRIANA FURON; NICOLE L. MCLAUGHLIN; IVAN LEE; JOHN BARBEAU; SUSANTHA JAYASUNDARA; GARY PARKIN; PETER Von BERTOLDI; JON WARLAND (Global Change Biology, 2007)
No‐tillage (NT), a practice that has been shown to increase carbon sequestration in soils, has resulted in contradictory effects on nitrous oxide (N 2 O) emissions. Moreover, it is not clear how mitigation practices for N 2 O emission reduction, such as applying nitrogen (N) fertilizer according to soil N reserves and matching the time of application to crop uptake, interact with NT practices. N 2 O fluxes from two management systems [conventional (CP), and best management practices: NT + reduced fertilizer (BMP)] applied to a corn ( Zea mays L.), soybean ( Glycine max L.), winter‐wheat ( Triticum aestivum L.) rotation in Ontario, Canada, were measured from January 2000 to April 2005, using a micrometeorological method. The superimposition of interannual variability of weather and management resulted in mean monthly N 2 O fluxes ranging from − 1.9 to 61.3 g N ha −1 day −1 . Mean annual N 2 O emissions over the 5‐year period decreased significantly by 0.79 from 2.19 kg N ha −1 for CP to 1.41 kg N ha −1 for BMP. Growing season (May–October) N 2 O emissions were reduced on average by 0.16 kg N ha −1 (20% of total reduction), and this decrease only occurred in the corn year of the rotation. Nongrowing season (November–April) emissions, comprised between 30% and 90% of the annual emissions, mostly due to increased N 2 O fluxes during soil thawing. These emissions were well correlated ( r 2 = 0.90) to the accumulated degree‐hours below 0 °C at 5 cm depth, a measure of duration and intensity of soil freezing. Soil management in BMP (NT) significantly reduced N 2 O emissions during thaw (80% of total reduction) by reducing soil freezing due to the insulating effects of the larger snow cover plus corn and wheat residue during winter. In conclusion, significant reductions in net greenhouse gas emissions can be obtained when NT is combined with a strategy that matches N application rate and timing to crop needs.